Detection of viable Mycobacterium avium subspecies paratuberculosis in powdered infant formula by phage-PCR and confirmed by culture - Botsaris, George; Swift, Benjamin M C; Slana, Iva; Liapi, Maria; Christodoulou, Maritsa; Hatzitofi, Maria; Christodoulou, Vasiliki; Rees, Catherine E D (International journal of food microbiology, 2016)
Surveys from different parts of the world have reported that viable Mycobacterium avium subsp. paratuberculosis (MAP) can be cultured from approximately 2% of samples of retail pasteurised milk samples. Pasteurised milk is used for the production of powdered infant formula (PIF) and therefore there is a concern that MAP may also be present in these products. Several studies have previously reported the detection of MAP in PIF using PCR-based assays. However, culture-based surveys of PIF have not detected viable MAP. Here we describe a phage amplification assay coupled with PCR (page-PCR) that can rapidly detect viable MAP in PIF. The results of a small survey showed that the phage-PCR assay detected viable MAP in 13% (4/32) of PIF samples. Culture detected viable MAP in 9% (3/32) PIF samples, all of which were also phage-PCR positive. Direct IS900 PCR detected MAP DNA in 22% (7/32) of PIF samples. The presence of viable MAP in PIF indicates that MAP either survived PIF manufacturing or that post-production contamination occurred. Irrespective of the route of MAP contamination, the presence of viable MAP in PIF is a potential public health concern.
Keywords: mléko; Mycobacterium avium subsp. paratuberculosis; Pasteurised milk; DNA, Bacterial; kojenec; Phage; polymerázová řetězová reakce; Polymerase Chain Reaction; Infant; Infant Formula; PCR; Paratuberculosis; DNA bakterií; náhražky mateřského mléka; Infant, Newborn; Powdered infant formula; novorozenec; zvířata; Humans; Bacteriophages; Rapid methods; Milk; bakteriofágy; lidé; Animals